Pengembangan Aplikasi Manajemen Pengajuan Kegiatan Dosen Studi Kasus Fakultas Ilmu Administrasi Universitas Brawijaya - Rikza Priyudha Hirdad; Bayu Priyambadha; Denny Sagita Rusdianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Brawijaya University's Faculty of Administrative Sciences (FIA UB) lecturers have activities besides providing lectures on campus, like lecturers who carry out their activities for faculty and personal needs. It causes several problems, the first is that there are a queue and accumulation of work rather than those are who have the authority to allow the activities. The second problem is the submission of the draft assignment letter can only be submitted after the submission of activities has been approved by the authorized party to approve it. The third problem is that the Activity Applicant sometimes forgets to report the results of activities and bookkeeping of the Accountability Letter (SPJ). Problems that have been mentioned, can affect the faculty and department accreditation activities, if there are incomplete files when it is needed. Also, the dean and staff want to know the activities and the event rather than the lecturers. To solve the problems developed a system that purposes to manage and make it easier to submit activities until reporting. By referring to the Procedure Operating System (POS), it can help the development of the system that will be developed. The system involves 7 actors, the needs of elicitation are producing 37 functional needs. The tests in this system include unit testing, integration testing, validation testing and compatibility testing of the system. The benefits that can be received from the Applicant are the ease of submitting activities and draft assignments because they do not work twice. Also, the Deans and their staff will be easier to know the activities of the Lecturers at FIA UB.